On the effects of glasses on the SAR in human head resulting from wireless eyewear devices at phone call state. (August 2018) - Lan, J.Q.; Liang, X.; Hong, T.; Du, G.H.
Abstract: This paper evaluates the effects of glasses on the specific absorption rates (SAR) in the human head resulting from wireless eyewear device at phone call state. We mainly concentrate on the SAR in the eyes since their sensitivity to electromagnetic fields (EMF). We find wearing glasses obviously alters the distribution and magnitude of the SAR. The maximal SAR in the ocular tissues with glasses is even 6 times more than that without glasses. Wearing glasses also induce the new hotspot in the eyes which may cause the biggest SAR increment in the ocular tissues. Moreover, calculated results indicate that the maximal SAR is sensitive to the size of glasses and radiation frequency. Because of this, we believe wearing glasses may possibly increase the risk of health hazard to eyes of wireless eyewear device user. These calculated results could be a valuable reference for the glasses designer to reduce the SAR in the eyes.